Сепаратизм як загроза національній безпеці Бельгії - Крук, А. П.; Романюк, Н. І.; Kruk, A. P.; Romaniuk, N. I. (Східноєвропейський національний університет імені Лесі Українки, 2014)
В статті розкрито зміст поняття «сепаратизм», з’ясовано історичні передумови прояву сепаратистських рухів у Бельгії. Проаналізовано сучасний стан сепаратизму як загрози національній безпеці Бельгії.

The paper addresses the problem of separatism in Belgium. The concept of «separatism» is defined, clarified the historical background of the manifestation of separatist movements in the country. The current state of the problem.
Separatism as a Threat to the National Security of Belgium
Keywords: сепаратизм; сецесія; міжнародні відносини; економічний сепаратизм; економічний розвиток; separatism; secession; international relations; economic separatism; economic development